In-hospital mortality of HIV-positive patients with acute kidney injury a decade after the roll-out of anti-retroviral therapy in Cape Town, South Africa - Chothia, Mogamat-Yazied; Ramsunder, Nikash (African Journal of Nephrology, 2019)
Background: Acute kidney injury (AKI) in HIV-infected patients in sub-Saharan Africa is a common cause of hospitalisation and is associated with high morbidity and mortality. There is a paucity of comparative data regarding the outcomes of AKI in those patients with and without HIV infection from the African continent. Methods: This was a single-centre retrospective study of all consecutive adult patients with AKI referred to the renal unit at Tygerberg Hospital for the period January 2015 to December 2016. The diagnosis of AKI required evidence of the following: a recent normal serum creatinine and/or normal kidney sizes on ultrasound examination and/or granular casts on urine microscopy. Kaplan–Meier curves and logistic regression were used to assess survival and identify factors predicting mortality. Results: We identified a total of 291 patients with AKI of whom 116 (40%) were HIV positive. HIV-positive patients had a mortality rate of 34.5% vs. 29.1% in the HIV-negative patients (P = 0.34). At hospital admission, HIV-positive patients had a higher admission serum creatinine (551 μmol/L vs. 190 μmol/L, P < 0.01). Of those who died, the HIV-positive patients were younger (41 vs. 52 years, P < 0.01), predominantly Black (87.5% vs. 23.5%, P < 0.01) and were mostly admitted to medical wards (92.5% vs. 41.2%, P < 0.01). There was no difference in mortality related to the use of renal replacement therapy (P = 0.50). Logistic regression identified mixed ancestry (OR 2.47, P = 0.02), HIV infection (OR 2.69, P < 0.01) and surgical ward admission (OR 2.05, P = 0.03) as predictors of death. Conclusions: In-hospital mortality of AKI was high, and HIV infection was associated with a greater risk of death. This may be the result of late presentation of both the AKI as well as the HIV infection.